CONTEMPORARY CONCEPTS OF MOLECULAR MECHANISMS OF THE PHYSIOLOGICAL AND TOXIC EFFECTS OF FLUORINE COMPOUNDS ON AN ORGANISM - Жукова, Анна Геннадьевна; Михайлова, Надежда Николаевна; Казицкая, Анастасия Сергеевна; Алехина, Дарья Александровна (Medicine in Kuzbass, 2017)
The review summarizes current literature data on the molecular mechanisms of the physiological and toxic effects of fluorine compounds on an organism.
Keywords: fluorine; oxidative metabolism; transcription; translation; intracellular alarm system